Islamic Parenting: Pendidikan Anak Menurut Ibnu Sina di Era Modern - Riansyah, Riansyah; Dewi, Eva; Pratama, Muhammad Surya (Peneliti.net, 2025)
The purpose of this research is to discuss and examine how human terms in the Qur'an. This study uses this research method, namely a qualitative method using library research, namely by reading, studying and examining books and sources of writing that are closely related to the problem discussed. The results of the discussion are basically education includes the principles of gender equality, gender bias in education results in the achievement of educational goals. For this reason, equitable education is needed where the curriculum of educational institutions integrates gender in subjects and lectures. One of the goals of education is how to create a just society, by not discriminating against one of the sexes. However, in reality, there is still discrimination in the world of education, so efforts are needed to overcome it, one of which is by formulating a curriculum with a gender perspective. The curriculum is a development of the vision and mission of educational institutions that want to realize educational goals. The gender-based curriculum is based on the assumption that women and men have equality in education and have equal opportunities